2020
DOI: 10.3390/ijerph17020613
|View full text |Cite
|
Sign up to set email alerts
|

Piercing and Oral Health: A Study on the Knowledge of Risks and Complications

Abstract: The aim of the present study is to verify the knowledge of risks and complications of oral piercings, and to observe the main complications associated with piercings, using a sample from central Italy of patients wearing intraoral piercings. Through piercing and tattoo studios selected randomly in Rome, Latina and Campobasso, and a tattoo and piercing convention in Latina, a group of 387 individuals with oral piercings were selected and asked to complete an anonymous questionnaire. After filling in questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 16 publications
(18 reference statements)
1
33
0
4
Order By: Relevance
“…6,[29][30][31][32] For example, in 2020, Covello et al found that periodic followups can even prevent oral piercing complications. 33 Only a minority of our participants used electric toothbrushes, which is consistent with the results of previous studies that showed a low frequency of electric toothbrush users among students and adults. 11,28 A previous study found that the majority of respondents did not consider electric toothbrushes to offer any greater advantage over manual toothbrushes.…”
Section: Discussionsupporting
confidence: 92%
“…6,[29][30][31][32] For example, in 2020, Covello et al found that periodic followups can even prevent oral piercing complications. 33 Only a minority of our participants used electric toothbrushes, which is consistent with the results of previous studies that showed a low frequency of electric toothbrush users among students and adults. 11,28 A previous study found that the majority of respondents did not consider electric toothbrushes to offer any greater advantage over manual toothbrushes.…”
Section: Discussionsupporting
confidence: 92%
“…Temos também que produtos como as pastas a base de carvão ativado podem tirar a atenção de produtos conhecidos, que realmente levam benefícios à saúde bucal como a pasta de dente convencional contendo flúor, fazendo o paciente substituir sua utilização por um produto de evidência científica ainda inconclusiva (Greenwall et al, 2019). De maneira geral os hábitos e acessórios nocivos influenciados pelas mídias sociais e prejudiciais à saúde bucal abordados podem causar cáries (Alhazmi et al, 2021;Sorooshian & Kamarozaman, 2018;Ziebolz et al, 2019;Covello et al, 2020), progressão da doença periodontal (Junco et al, 2017;Covello et al, 2020;Sorooshian & Kamarozaman, 2018;Ziebolz et al, 2019;Schmidt et al, 2019) e alterações em tecido gengival (Sorooshian & Kamarozaman, 2018;Schmidt et al, 2019;Covello et al, 2020;Junco et al, 2017;King et al, 2018). A alteração em comum encontrada entre os três hábitos/acessórios nocivos estudados (Carvão ativado, Aparelhos da Moda e Piercing oral) foi a influência sob a doença periodontal (Junco et al, 2017;Covello et al, 2020;Sorooshian & Kamarozaman, 2018;Ziebolz et al, 2019;Schmidt et al, 2019;Greenwall et al, 2019).…”
Section: Discussionunclassified
“…Acerca do uso de piercing oral, percebe-se que a sua utilização implica no surgimento de inúmeras complicações orais (King et al, 2018) representando um risco a saúde bucal (Covello et al, 2020) e causando efeitos imediatos e a longo prazo (Junco et al, 2017), observa-se também que pacientes que usam o adorno demonstram pior condição de saúde dental e periodontal em relação aos que não o utilizam (Ziebolz et al, 2019). As principais alterações bucais encontradas em pacientes que utilizam o acessório segundo a análise dos 6 artigos encontrados sobre o tema foram a recessão gengival (Ziebolz et al, 2019;Junco et al, 2017;Covello et al, 2020;King et al, 2018;Ziebolz et al, 2019;Schmidt et al, 2019) e a presença de alterações periodontais (Ziebolz et al, 2019;Junco et al, 2017;Covello et al, 2020;Ziebolz et al, 2019;Schmidt et al, 2019) sendo estas as principais alterações citadas em comum em ambos os estudos.…”
Section: Discussionunclassified
“…Body piercing has become very popular in the past two decades, and it has been reported that approximately 50% of millennials receive at least one non-earlobe piercing [ 1 , 2 ]. As most of these piercings are not performed in clinical settings, 17–46% of the piercings lead to complications [ 3 , 4 ] including infection, metal allergy, bleeding, and tissue scarring [ 4 , 5 , 6 , 7 ]. Among all these problems, local infection has been reported to be the most common type of piercing complication [ 6 ].…”
Section: Introductionmentioning
confidence: 99%